Action of growth regulators and plant stimulants on germination of maize and tomato seeds - Castro, Paulo R.C.; Henrique, Ana A.; Fumis, Terezinha F.; Babboni Júnior, Antonio C.; Minarelli, Angela M.; Di Stasi, Luiz C.; Rodrigues, Selma D. (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1987)
This study was carried out to determine the effects of gibberellic acid 100 ppm, chlormequat 2000 ppm, maleic hydrazide 1000 ppm, Agrostemmin 1.25 g.l-1 and Atonik (1:2000) 0.5 ml.l-1 on germination of Zea mays cv. Cargill -525 and Lycopersicon esculentum cv. Kada seeds, under laboratory conditions. Measurements realized 7 and 15 days after sowina in Petri dishes with 10 ml of chemicals solution, showed that gibberellic acid and Agrostemmin increased radicle and hypocotyl growth of maize and tomato. Maleic hydrazide inhibited radicle growth of maize. Maleic hydrazide and Atonik showed a tendency of reduced radicle and hypocotyl growth of tomato seedlings.